The Association between the Number of Vacuum Pop-Offs and Adverse Neonatal Outcomes - Sakowicz, Allie; Zahalka, Salwa J.; Miller, Emily S. (American Journal of Perinatology, 2021)
Objective Obstetrical vacuum manufacturers have long recommended a maximum of two to three pop-offs be allowed before abandoning the procedure. However, there is a paucity of evidence on the safety of vacuum-assisted vaginal delivery in relation to the number of pop-offs to support this recommendation. Our objective was to examine whether the number of pop-offs in a vacuum-assisted vaginal delivery was associated with adverse neonatal outcomes.Study Design This is a retrospective cohort study of women who underwent a trial of a vacuum-assisted vaginal delivery at a single tertiary care institution between October 2005 and June 2014. Maternal and fetal factors associated with the number of pop-offs were examined in bivariable analyses. Multivariable analyses were performed to determine the independent association of the number of pop-offs with adverse neonatal outcomes.Results Of the 1,730 women who met inclusion criteria, 1,293 (74.7%) had no pop-offs, 240 (13.9%) had one pop-off, 128 (7.4%) had two pop-offs, and 69 (4.0%) had three or more pop-offs. Neonatal scalp/facial lacerations, intracranial hemorrhage, seizures, central nervous system depression, and neonatal intensive care unit admission were all associated with the number of pop-offs in bivariable analyses. In multivariable analyses, compared to no pop-offs, having any vacuum pop-offs was associated with an increased odds of adverse neonatal outcomes. However, there was not a consistent dose–response relationship.Conclusion While having vacuum pop-offs in a vacuum-assisted vaginal delivery was associated with an increased risk of adverse neonatal outcomes, there did not appear to be a dose-dependent association with the number of pop-offs.Key Points
Keywords: vacuum-assisted vaginal delivery; vacuum; pop-off; dislodgment; detachment; obstetrician